Violent Politics : A History of Insurgency, Terrorism & Guerrilla War, From the American Revolution to Iraq - Polk, William R. 1929- (New York Harper Collins Publishers, 2007)
An examination of the role of insurgent tactics in world conflicts throughout the past two-and-a-half centuries places current issues in a context of world history while covering events that marked such examples as the war in Iraq.
Include Index
Keywords: Terrorism -- Insurgency -- Guerrilla warfare